(untitled) (Journal of Dhaka National Medical College & Hospital, 2024)
Background: Early risk stratification of patients with myocardial infarction is critical to determine optimum treatment strategies and enhance outcomes. The present study was therefore undertaken to determine the relationship between QRS duration (QRSd) on admission ECG and left ventricular ejection fraction (LVEF) as a measure of left ventricular function in non-ST elevated myocardial infarction (NSTEMI) patients. Methods: This observational study was carried out from January to December 2020 with total of 120 patients with a history of NSTEMI. Based on the cut-off value of QRS duration 100 msec, the patients were divided into two groups-one group with QRS duration ≤100 msec (normal QRS) and another group with QRS duration> 100 msec (prolonged QRS). Left ventricular systolic function was considered preserved, if it was 252% and reduced if it was < 52%. The association and correlation between QRS duration and LVEF was then observed. Results: The prevalence of reduced LVEF in patients with prolonged QRS duration (> 100 msec) was double (38%) than that of preserved (19.5%). The risk of having LV dysfunction in patients with prolonged QRS duration was 2.5 (95% CI=1.1-6.2) times higher than that in patients normal QRS duration (d" 100 msec) (p=0.039). The QRS duration and LVEF bear a significantly inverse relationship (r=-0.341, p<0.001). The sensitivity of prolonged QRS duration (> 100 msec) in correctly detecting LV dysfunction was inappreciably low (38%), although its specificity in excluding those who did not have LV dysfunction was optimum (80.5%) with overall diagnostic accuracy being 52.5% Conclusion: Prolonged QRS duration on a standard 12-lead ECG is associated with reduced echocardiographic LVEF. However, QRS duration in predicting LV dysfunction is much less sensitive, although its specificity is optimum indicating that QRS duration is not a good predictor of LV dysfunction (reduced LVEF), but it can dependably predict those who do not have LV dysfunction (preserved LVEF). J. Dhaka National Med. Coll. Hos. 2024; 30 (01): 23-28